Geometric and Mathematical Patterns in The Architecture of The Grand Mosque of Syekh Yusuf Gowa: An Exploration - Dewi Sartika; Firiani Nur; Nur Yuliany (Jurnal Pendidikan Matematika (JPM), 2025)
Ethnomathematics studies the relationship between mathematics and culture, including its application in everyday life. One of the relevant cultural objects is the mosque, which can be an interesting approach in learning mathematics. This study aims to explore the application of geometric concepts and mathematical patterns in the architectural design of the Grand Mosque of Syekh Yusuf Gowa. Using a qualitative approach with ethnographic methods, data were collected through observation, documentation, and literature review. The results of the study show that the structure and ornaments of the mosque reflect various geometric elements, such as two-dimensional shapes (square, circle, triangle, rhombus, octagon, and trapezoid) and three-dimensional shapes (cylinder and quadrilateral pyramid). In addition, geometric transformations such as reflection, translation, and dilation are also found in the design. There are also mathematical patterns that enrich the aesthetics of the architecture. These findings underline the importance of the integration of mathematics and culture in education, and provide new insights into the application of mathematical concepts in traditional architecture. This study confirms that the architecture of the Grand Mosque of Syekh Yusuf is not only a place of worship, but also a source of inspiration in learning mathematics.